Estimation of thermoelectric power generation by recovering waste heat from Biomass fired thermal oil heater. (1st July 2015) - Barma, M.C.; Riaz, M.; Saidur, R.; Long, B.D.
Highlights: Thermoelectric power generation from thermal oil heater exhaust is estimated. Different thermoelectric materials are investigated for maximizing output power. Bismuth telluride has been found the best TE material to apply in this application. The estimated annual output power is 181, 209 kW h from the proposed system. Abstract: This study reports estimation of the amount of electrical power produced by thermoelectric generator (TEG) placed between flue gas duct and fresh air duct of an industrial thermal oil heater. Plate fin heat sink on hot and cold side of the TEG module was inserted into the flue gas and fresh air duct respectively. The effect of various design parameters, flow parameters were investigated in order to maximize the electrical power generation. Then the best suited conditions were applied to new thermoelectric generator module based on recently developed thermoelectric materials. A Bi2 Te3 based commercial module (HZ-2) produce 3.7 W, where new module, based on p- type (Bi, Sb)2 Te3 and n- type hot forged Bi2 Te3 generate 4.4 W, at the same operating condition, which is about 19% improvement in output electrical power compared to commercial module. Estimated annual electrical power generation from this proposed system could be around 181, 209 kW h. Thermal efficiency of the TEG modules based on recently developed thermoelectric materials could be enhanced up to 8.18%. The specifications of plate fin heat sinks as well as thermoelectric properties of the p-n materials of the system have substantial impact on the performance of TEG module.